2017
DOI: 10.1088/1361-665x/aa516c
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric microcapsules with switchable mechanical properties for self-healing concrete: synthesis, characterisation and proof of concept

Abstract: Microcapsules, with sodium silicate solution as core, were produced using complex coacervation in a double, oil-in-water-in oil, emulsion system. The shell material was a gelatin-acacia gum crosslinked coacervate and the produced microcapsules had diameters ranging from 300 to 700 μm. The shell material designed with switchable mechanical properties. When it is hydrated exhibits soft and 'rubbery' behaviour and, when dried, transitions to a stiff and 'glassy' material. The microcapsules survived drying and reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 28 publications
1
83
0
Order By: Relevance
“…Similarly, the investigation of more thermally stable materials like polyurea has led to the development of capsules ( Figure b) for survivability in elevated temperature environments . A different approach included the production of microcapsules with switchable mechanical properties to ensure survivability during the concrete mixing process. In this context, recent collaboration between universities and companies led to the design and production of microcapsules that exhibit ductile “rubbery” behavior when hydrated and when dried transition to stiff, brittle glass‐like behavior (Figure a) …”
Section: Encapsulated Autonomous Self‐healing (Polymers or Minerals)mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the investigation of more thermally stable materials like polyurea has led to the development of capsules ( Figure b) for survivability in elevated temperature environments . A different approach included the production of microcapsules with switchable mechanical properties to ensure survivability during the concrete mixing process. In this context, recent collaboration between universities and companies led to the design and production of microcapsules that exhibit ductile “rubbery” behavior when hydrated and when dried transition to stiff, brittle glass‐like behavior (Figure a) …”
Section: Encapsulated Autonomous Self‐healing (Polymers or Minerals)mentioning
confidence: 99%
“…Recent research activities in microencapsulation for self‐healing in cementitious systems: a) gum Arabic/gelatin shell microcapsules containing sodium silicate core, b) polyurea shell microcapsules produced containing semicrystalline sodium silicate, c) schematic of the microfluidics process including the photopolymerization process, d) a laboratory setup of double emulsion flow focusing microfluidics platform, e) optical microscope image of microfluidics produced monodisperse acrylate microcapsules and f) corresponding surface functionalized acrylate microcapsules . Reproduced with permission . Copyright 2017, IOP publishing.…”
Section: Encapsulated Autonomous Self‐healing (Polymers or Minerals)mentioning
confidence: 99%
“…The results of thermalgravimetric analysis test showed that the mass loss of microcapsules is very small even at 180 °C and the morphology is intact, indicating the microcapsule can resist the high‐temperature condition during the mixing and compaction process after being added to the cementitious material. In 2017, Kanellopoulos et al investigated the geometry of microcapsules between wet and dry conditions. It was found that there was no effect on the structural integrity of the shell under the dehydration/rehydration cycles test.…”
Section: Applications In Shmmentioning
confidence: 99%
“…Alongside this work on autogenous healing has been a major research effort on autonomic (manufactured) healing systems . The three main techniques explored for delivering and releasing healing agents are as follows: i)The embedment of brittle vessels (normally tubes) into structural elements; ii)The addition of microcapsules into cementitious mixes; iii)The creation of interconnected channels or “vascular networks” within cementitious structural members …”
Section: Overview Of Existing Self‐healing Technologies and Mechanismsmentioning
confidence: 99%